الدبلجة بين الإنتقاء والرقابه - عاصف حسنه (Maalim, 2018)
ملخص يعد استخدام الدبلجة بشكل واسع في معظم انحاء العالم ظاهرة تستحق منا الوقوف والتركيز عليها حيث أن هذه العملية المهمة ليست مجرد نقل من لغة الى اخرى ولكنها عمليه ادخال ثقافات ومعتقدات مختصة ببلد بعينها الى بلاد اخرى وهذا يستحق منا التوضيح والشرح لعملية النقل وكيفية الانتقاء وهل يوجد رقابة وغربلة للأعمال قبل عرضها . لابد ان نأخذ في عين الاعتبار أن كثيرا من الدول تدبلج الاعمال إلى لغاتها الاصلية من أجل الحفاظ على هويتها ولهجتها المحلية مثل معظم دول اوروبا. اما في الوطن العربي فهناك العديد من الملاحظات حول الدبلجة حيث أن هناك عوامل كثيرة تؤثر عليها ومنها نقطتين أساسيتين هما سياسة اختيار مادة الدبلجة في العالم العربي وطريقة الدبلجة و دور الرقابة الزائف . بالنسبة للسياسات التي يتخذها عالمنا العربي من أجل اختيار الاعمال فأكاد أجزم أنه لا توجد سياسات موحدة تهتم بالهوية العربية وثقافتها و تحافظ على موروثاتنا فالكل يسعى للكسب بدون مراعاه لأي ضوابط . وهناك آراء كثيرة حول هذا الموضوع حيث أن البعض يرجح أن الدبلجة ما هي إلا عملية تجارية بحتة وأخرون يعترفون بأنها دلاله على الكسل المزمن عند الشعوب العربية وهناك رأي آخر بأن العلة في الانتاج حيث أن الانفاق المالي قليل ولذلك يستسهلون الدبلجة. لابد ان نعترف أن تأثير الدبلجة سلبي بشكل كبير وخاصة منذ انتشار دبلجة المسلسلات الكرتونية اليابانية وبعدها الدراما المكسيكية وتلتها الدراما التركية والهندية التي غزت كل أرجاء الوطن العربي وبثت كل ثقافاتها المحلية السلبية بالأخص داخل مجتمعنا حيث أن المجتمع العربي يميل للتقليد أكثر من الاحتفاظ بثقافته الاصيلة. بالرغم من أن بعض الآراء الأخرى تميل إلى أن الدبلجة تعد نعمة حيث أنها كسرت حواجز اللغة والترجمة وفتحت الأعين على ثقافات وعادات الشعوب الاخرى وقربت المسافات وجعلتنا نتعرف على مختلف الثقافات في بلدان بعيدة عنا. في السنوات الاخيرة شاهدنا فيضانات من المسلسلات المدبلجة ومن أهمها المسلسلات التركية التي حققت نسب نجاح مذهلة في عالمنا العربي بل واصبحت حديث الشارع العربي كما أنها عززت من الاقتصاد التركي حيث زادت نسبة السفر للسياحة في تركيا مئات المرات طوال العام وبالأخص في الصيف وهذا عمل على ارتفاع ونهوض الاقتصاد التركي وجعلهم يكثرون من الانتاجات الضخمة التي ابهرت العرب حيث أنهم ينبهرون بكل ما هو من الخارج أما الاقتصاد العربي ففي هبوط حاد ومستمر ولم يع المنتجون بهذه الآفة بل كل تفكيرهم في الربح السريع وأخيرا كل ما نستطيع أن نقوله عن هذه الظاهرة بأنها صارت مثل خيوط العنكبوت الذي قفز على عالمنا وبدى كأنه مسكين وضعيف حتى نسج خيوطه الرقيقة الملمس الحادة التأثير ونصب شباكه فوق العالم العربي ليغطيه بالكامل ويحجب عنا رؤية الشمس التي تنير لنا طريقنا ويجعلنا نرى فقط ما ينشره ويبثه لنا . واذا لم تتحرك الجهات المنتجة لتحفيز الابداع الفكري وبدأ عمليات انتاج ضخمة توازي ما نشاهده من أعمال مدبلجة سوف نندثر وتختفي معالمنا ونصبح كلنا مصبوغين بنفس اللون الرمادي الباهت الذي لا حول له ولا قوة. Abstract The widely use of dubbing in most parts of the world is a phenomenon worthy to stand and focus on as this important process is not just a transfer from one language to another, but it is the process of introducing cultures and beliefs of a specific country to another country and it deserves to be clarified to explain the transfer process and how to select, to control and to screen the works before presentation. We must bear in mind that many countries are dubbing drama into their original languages in order to preserve their local identity and language, like most European countries. In the Arab world, there are many remarks on dubbing, as there are many factors affecting them, including two main points: the policy of selecting dubbing material in the Arab world and the method of dubbing and the role of false censorship. As for the policies taken by our Arab world for the choice of the works to be dubbed , I am sure that there are no unified policies that concern the Arab identity and culture and preserve our heritage. Everyone seeks to gain without any restrictions. There are many opinions on this subject as some are likely to dubbing is purely a commercial process and others admit that it is indicative of the chronic laziness among the Arab peoples and there is another view that the bug in production as the financial expenditure is little and therefore easy to dubbing. We have to admit that the influence of dubbing is very negative especially since the spread of dubbing of Japanese cartoon series followed by the Mexican drama, the Turkish and Indian dramas that invaded the entire Arab world and broadcast all of their negative local culture especially within our society. The Arab society tends to imitate tradition more than to preserve its original culture. Although some other opinions suggest that dubbing is a blessing as it breaks language and translation barriers and opened the eyes to the cultures and customs of other peoples and approached distances and made us recognize the different cultures in countries far from us. In the last years, we have seen floods of soap operas, the most important of which are the Turkish soap operas, which have achieved amazing success rates in the Arab world, and have become the talk of the Arab street. They also boosted the Turkish economy. Turkey's tourism has increased hundreds of times throughout the year, especially in the summer. The Turkish economy and make them abound of the huge productions that dazzled the Arabs as they are impressed with everything that is from the outside The Arab economy in a sharp decline and continued not aware of the producers of this scourge, but all their thinking in the quick profit. Finally, all we can say about this phenomenon is that it has become like a spider web that has jumped on our world and has appeared to be so poor and weak that we have woven its thin, sharp-edged threads and spread its leaves over the Arab world to cover it completely and block us from seeing the sun that lights our way and makes us see only what it publishes and transmits for us . If the producers do not move to stimulate intellectual creativity and start production processes parallel to what we have seen in dubbed works, we will disappear and our features will be faint and we will become all dyed in the same gray color which is dull and powerless.